The role and host-directed targeting of long non-coding RNAs in macrophage polarization during Mycobacterium tuberculosis infection - Pillay, Shandré (Department of Clinical Laboratory Sciences, 2022)
In 2020, the World Health Organization (WHO) reported 1.5 million tuberculosis (TB)- associated deaths and an incidence of 10 million new cases. The causative, Mycobacterium tuberculosis (Mtb), evades host immune responses by skewing macrophage polarization towards a less microbicidal alternative state to avoid classical effector killing functions. However, the molecular details underlying these evasion mechanisms remain incomplete and current therapy is challenged with drug resistance. Host-directed therapy (HDT) has recently gained attention, with long non-coding RNAs (lncRNAs) as potential targets due to their emerging roles in pathogenic immune responses. We previously performed cap analysis gene expression (CAGE) transcriptomics on IFN-γ stimulated (classically activated) and IL-4/IL-13 stimulated (alternatively activated) mouse macrophages, identifying 151 differentially expressed lncRNAs following Mtb infection. We validated the top 11 differentially expressed lncRNAs and two were chosen for this study, lncRNA-125, whose expression was regulated at different levels unstimulated and in response to IFN-γ and IL-4/IL-13, and lncRNA-612 whose expression was only induced by IFN-γ stimulation. Interestingly, the expression of lncRNA125 and lncRNA-612 was downregulated following Mtb infection. Therefore, this study aimed at functionally validating these lncRNAs in unstimulated, IFN-γ and IL-4/IL-13 stimulated and/or Mtb-infected mouse and human macrophages by a loss-of-function approach using chemically engineered antisense oligonucleotides (gapmeRs). Knockdown of lncRNA-125 by gapmeRs reduced Mtb growth and anti-inflammatory cytokine production mediated by increased apoptosis, nitrite and pro-inflammatory cytokine production in IL-4/IL-13 prestimulated mouse macrophages. Whereas knockdown of lncRNA-125 in IFN-γ pre-stimulated mouse macrophages favoured Mtb growth and anti-inflammatory cytokine production, with reduction of apoptosis, nitrite and pro-inflammatory cytokine production. Therefore, indicating that lncRNA-125 regulates macrophage polarization during Mtb infection. Knockdown of lncRNA-125 in human macrophages resulted in reduced Mtb growth and increased proinflammatory cytokine production in unstimulated, IFN-γ and IL-4/IL-13 pre-stimulated BMDMs infected with Mtb. Comparatively, gapmeR knockdown of lncRNA-612 reduced Mtb growth and increased pro-inflammatory cytokine production in IFN-γ pre-stimulated mouse and human macrophages. In mouse macrophages, these responses were mediated by increased apoptosis and nitrite production, with reduced anti-inflammatory cytokine production. Overall, these findings highlight lncRNAs as novel host factors to be further investigated as targets for TB diagnostics and adjunctive HDTs.